2014
DOI: 10.3109/03602532.2014.883406
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of carbon nanotubes and graphene: the utility of carbon-based nanoparticles in nanomedicine

Abstract: Carbon-based nanomaterials have attracted great interest in biomedical applications such as advanced imaging, tissue regeneration, and drug or gene delivery. The toxicity of the carbon nanotubes and graphene remains a debated issue although many toxicological studies have been reported in the scientific community. In this review, we summarize the biological effects of carbon nanotubes and graphene in terms of in vitro and in vivo toxicity, genotoxicity and toxicokinetics. The dose, shape, surface chemistry, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(69 citation statements)
references
References 94 publications
1
68
0
Order By: Relevance
“…/10717544.2016 (SWNT) or multiple layer (MWNT) (Lin et al, 2004;Liu et al, 2009). They undergo membrane penetration and cell internalization through a spiraling or winding motion as well as through strong interactions with various proteins (Zhang et al, 2014b). Graphene (G) is single-layered six-sp 2 -carbon atom organized in a two-dimensional honeycombed network (Rao et al, 2009;Wang et al, 2011), up taken by cells via direct penetration events (e.g.…”
Section: Carbon Nanostructures and Nanohybridsmentioning
confidence: 99%
“…/10717544.2016 (SWNT) or multiple layer (MWNT) (Lin et al, 2004;Liu et al, 2009). They undergo membrane penetration and cell internalization through a spiraling or winding motion as well as through strong interactions with various proteins (Zhang et al, 2014b). Graphene (G) is single-layered six-sp 2 -carbon atom organized in a two-dimensional honeycombed network (Rao et al, 2009;Wang et al, 2011), up taken by cells via direct penetration events (e.g.…”
Section: Carbon Nanostructures and Nanohybridsmentioning
confidence: 99%
“…This would allow for reducing the drugs dosage, their concentrations on sites that are not of interest, and the side effects associated with chemotherapy and hormonal therapy [15,16]. In this regard, carbon nanomaterials with potential uses for the administration of drugs against cancer and breast cancer are being analyzed [17,22,23,[29][30][31]; they are considered as advantageous systems to control drug release in the organism and increase the efficiency of treatments and reduce their toxicity [17,32,33]. However, carbon nanomaterials have some disadvantages including their lack of solubility and low reproduction rate through their chemical functionalization and structural characterization.…”
Section: Drug Releasementioning
confidence: 99%
“…However, carbon nanomaterials have some disadvantages including their lack of solubility and low reproduction rate through their chemical functionalization and structural characterization. Furthermore, their use in medicine is widely tested due to their potential toxicity [32][33][34][35][36][37][38][39].…”
Section: Drug Releasementioning
confidence: 99%
“…It has been shown that carbon nano-formulations can be used for various applications such as cancer diagnosis, imaging, targeted photothermal therapy, photoacoustic imaging, drug delivery and tissue engineering (Zhang et al 2014). Carbon NP can be classified into two groups, including carbon nanotubes (CNT) and carbon nanohorns (CNH).…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%